2007
DOI: 10.1111/j.1365-2672.2006.03062.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors influencing the rate of germination of spores of Bacillus subtilis by very high pressure

Abstract: Aims: To elucidate the factors that determine the rate of germination of Bacillus subtilis spores with very high pressure (VHP) and the mechanism of VHP germination. Methods and Results: Spores of B. subtilis were germinated rapidly with a VHP of 500 MPa at 50°C. This VHP germination did not require the spore's nutrient-germinant receptors, as found previously, and did not require diacylglycerylation of membrane proteins. However, the spore's pool of dipicolinic acid (DPA) was essential. Either of the two redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
98
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 37 publications
5
98
1
1
Order By: Relevance
“…Germination was also performed on non-heat-activated spores at an OD 600 of 1 in 50 mM Tris-HCl (pH 7.5) buffer either at 37°C with 150 MPa of pressure or at 50°C with 500 MPa of pressure (4,5,24,36). The extent of spore germination due to pressure was analyzed by flow cytometry after staining with Syto 16 (4).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Germination was also performed on non-heat-activated spores at an OD 600 of 1 in 50 mM Tris-HCl (pH 7.5) buffer either at 37°C with 150 MPa of pressure or at 50°C with 500 MPa of pressure (4,5,24,36). The extent of spore germination due to pressure was analyzed by flow cytometry after staining with Syto 16 (4).…”
Section: Methodsmentioning
confidence: 99%
“…Heat-activated spores (10-l aliquots [ϳ10 5 spores]) containing kanamycin (50 g/ml) to prevent cell growth were spotted on the slides, a glass coverslip was added and sealed with clear nail polish to prevent the slide from drying, and ϳ100 spores on the slide were examined by phase-contrast microscopy during incubation at 37°C. Control experiments demonstrated that the addition of kanamycin did not affect rates of spore germination.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with possible roles of nutrient germinant receptor levels and/or heat activation temperature optima in affecting spore superdormancy, since neither dodecylamine nor Ca-DPA triggers Bacillus spore germination through nutrient germinant receptors, and germination with these agents is also not stimulated by heat activation (11,15,17). However, the effects of high pressures, peptidoglycan fragments, and bryostatin, all of which almost certainly trigger spore germination by mechanisms at least somewhat different than triggering of germination by nutrients, dodecylamine, and Ca-DPA (2,3,11,15,20,22,23), have not been tested for their effects on superdormant spores. Consequently, we have compared the germination of dormant and superdormant spores of two Bacillus species by high-pressures, peptidoglycan fragments, and bryostatin.…”
mentioning
confidence: 99%